Are video games the best way to stay-at-home? - Damar Kristanto; M. Nilzam Aly; Bambang Suharto; Rahmat Yuliawan; Aji Akbar Firdaus (Universitas Airlangga, 2021)
The COVID-19 pandemic has disrupted many aspects of normal social life. The community is required not to leave the house too much if it is not necessary. Often during times of independent isolation or in personal cases, people are afraid to leave the house. They are faced with boredom so this is an opportunity for the digital entertainment industry to develop. On the other hand, many violations of COVID-19 health protocols still occur in society and people are still reluctant to stay-at-home. The question is what medium is good for persuasion as well as giving pleasure to people to entertain themselves during independent isolation and with low levels of boredom. Video games are a growing industry during the COVID-19 pandemic, unfortunately, this media has not been widely used as a means of persuading people to obey health protocols and stay-at-home. This study shows a correlation between gaming activity and the tendency not to leave the house. Besides, what types of games have the potential to keep someone from leaving the house are also discussed in this paper.